Gouvernance des politiques de relocalisation face au risque de montée du niveau de la mer - Hélène Rey-Valette; Bénédicte Rulleau (Développement Durable et Territoires)
Sea-level rise related to climate change will tend to increase the risk of marine inundation. The sustainability of beaches, which are a natural strategic asset for coastal zones given the recreational and storm protection services that they provide, may be threatened. This article addresses the local governance conditions for adaptation policies through the case of relocation which is one of the recommended measures for adaptation to sea level rise. In addition to the funding issue, the local governance conditions for these policies are addressed through a review of arrangements that would support the implementation of relocation. The article focuses in particular on the contribution of the recent concept of libertarian paternalism which orients towards agents towards well-being promoting public interventions.